CLIMATE ANALYSIS OF THE MUNICIPALITIES OF PORTALEGRE/RN AND FRANCISCO DANTAS/RN - Amorim, José Robson; Medeiros, Jacimaria Fonseca de (Geosaberes; Vol 13 (2022), 2022)
Inserted in a large continent and with different atmospheric agents in force, the Brazilian Northeast (NEB) is characterized by being an area with climatic specificities, with high temperatures and irregular precipitation. Still in this context is Rio Grande do Norte (RN) and, consequently, the study area of ​​this work. A climatic analysis was carried out, over a period of 30 years (1973 - 2002), of the municipalities of Portalegre and Francisco Dantas, located in the Oeste Potiguar mesoregion and where exceptions are evident regarding the climate. For the methodology, the methodological framework of Medeiros (2016) was used and as bibliographic reference, concepts used by Schmidt (2014), Mendonça and Danni-Oliveira (2007), Ayoade (2016), Reboita et al. (2012), among others. Regarding the data, rainfall data were made available by EMPARN and temperature data were estimated using software, following the model of Cavalcanti and Silva (1994), called Estima_T and which provides the averages, maximum and minimum values ​​based on latitude, longitude and altitude. After data tabulation, the climatological water balance was generated, according to the model proposed by Thornthwaite and Mather (1955). For Portalegre the rainfall average was 929.52 mm and 23.22 ºC as a thermal average. Francisco Dantas, on the other hand, the average precipitation value found was 823.73 mm and his thermal average is 26.61 ºC. From the data generated in the water balance, we have the formulas C1wA '(Dry Subhumid Megatherm, with moderate water surplus in summer) for Portalegre and C1dA' (Dry Subhumid Megatherm with little or no water surplus) for Francisco Dantas. Keywords: Climate. Hydric balance. Climatic Typology.